“Pregnant Time”: The Messianic Performativity of the Madres de Plaza de Mayo a7nd the 15-M Movement - Ferreira, Maria (Stasis, 2014)
Scholars around the world have discussed the ontological possibilities of transnational social movements. This article addresses these possibilities, highlighting how two renowned social movements have (re)constructed time as an ontological category through their performative activities and publicly argued beliefs. Departing from Giorgio Agamben’s work on messianic time, the article discusses how the Madres de Plaza de Mayo and the Spanish 15-M Movement (also known as the Indignados), have tried to recover the allegedly lost subjectivity of their members through the refusal to act in keeping with linear conceptions of time. These movements have tried to seize time and retrieve political personhood through particular spatial and temporal performativities. Both movements, which emerged in particularly traumatic historical periods, embody a non-linear and messianic understanding of time. The article argues, however, that the movements have translated this non-linear understanding of time through different messianic resources, namely, particular temporal and spatial performativities.